ANALISIS GETARAN STRUKTUR SANDWICH DENGAN AUXETIC CORE PADA BIDANG NON- PLANAR - Samuel Aditya, Yitro
One type of composite material is a sandwich structure which is commonly used in aircraft because it has high structural strength combined with light mass. Sandwich structure consists of face sheets and a core that generally has a geometric shape resembling a honeycomb. Another variation that can be used as a core of sandwich structure is an auxetic material which has a negative poisson's ratio that offer valuable enhancement of mechanical properties. This research studies the characteristics of out-of-plane auxetic core sandwich structure when subjected to vibration. This is important because vibration phenomena often occur in airplanes and can cause structural failures. In this study, the auxetic core is modeled as a 2D re-entrant geometry. In the finite element simulation process, several simplifications were carried out such as using PLA material which is assumed to be an isotropic material and ignoring the adhesive connection in the sandwich structure. From the simulation results, it is found that the sandwich structure has a lower natural frequency than homogeneous rods with a difference of 27.5 Hz. The parametric study was initiated by varying the geometry of the re-entrant cells. The results of the parametric study showed that the sandwich structure had the highest natural frequency on the re-entrant cells with ? = -5?. However, the natural frequency of sandwich structures as a result of parametric studies is lower than homogeneous beam with a difference of 0.5 Hz. This result is considered effective because with a fairly low natural frequency difference, an out-of-plane auxetic core sandwich structure has a lighter mass than a homogeneous beam with a mass difference of up to 40.7%.